2019
DOI: 10.1038/s41598-019-41952-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional neutralization of anti-IFN-γ autoantibody in patients with nontuberculous mycobacteria infection

Abstract: Interferon (IFN)-γ is crucial for normal immune surveillance and exhibits immunomodulatory, antimicrobial, and anticancer activity. Patients with nontuberculous mycobacteria (NTM) infection commonly express high levels of anti-IFN-γ autoantibodies (autoAbs) and suffer from recurrent infections due to adult-onset immunodeficiency with defects in IFN-γ immune surveillance. In this study, we developed the methods for determination of anti-IFN-γ autoAbs and then characterized their neutralizing activity in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 17 publications
5
47
0
Order By: Relevance
“…The patients with NTM infection more likely showed defect in signal transduction of IFN-γ/IL-12 axis, especially in patients with disseminated NTM diseases 14 . Besides, the patients with NTM infection commonly express high levels of anti-IFN-γ autoantibodies and suffer from recurrent infection 15,16 . www.nature.com/scientificreports www.nature.com/scientificreports/ NTM was more likely to infect older females as reported previously 1,17,18 ; this may suggest that estrogen has a protective role against NTM 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The patients with NTM infection more likely showed defect in signal transduction of IFN-γ/IL-12 axis, especially in patients with disseminated NTM diseases 14 . Besides, the patients with NTM infection commonly express high levels of anti-IFN-γ autoantibodies and suffer from recurrent infection 15,16 . www.nature.com/scientificreports www.nature.com/scientificreports/ NTM was more likely to infect older females as reported previously 1,17,18 ; this may suggest that estrogen has a protective role against NTM 18 .…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 81% of patients with recurrent non-tuberculous mycobacterial infections have high levels of anti-IFNγ neutralizing antibodies, and decreased levels of serum IFNγ. Krisnawati et al demonstrated that these patients' serum blocked IFNγ activation of STAT1 and transactivation of IRF1 [36]. Some, but not all anti-IFNγ antibodies bound to a major epitope region (amino acid residues 121-131) required for IFN receptor activation.…”
Section: Deleterious Effects Of Acaasmentioning
confidence: 99%
“…Patients affected by "Adult-onset immunodeficiency with susceptibility to mycobacteria", belong to the category "Phenocopies of inborn errors of immunity", produce autoantibodies against IFN-γ and have increased susceptibility to NTM [84,[98][99][100][101][102][103][104][105][106][107][108].…”
Section: Immunodeficienciesmentioning
confidence: 99%